A Case Report on Life-Threatening Lower Gastrointestinal Bleeding: A Rare Presentation of Mucinous Adenocarcinoma of the Appendix - H. W. T. D. Wijayaratne; K. J. A. Fernando; T. Matheeshan (Case Reports in Surgery)
Introduction. A life-threatening lower gastrointestinal bleeding from mucinous adenocarcinoma of the appendix is a rare occurrence. Diagnosing and management of such a condition are challenging. Case Presentation. A 73-year-old male with a history of type 2 diabetes mellitus and hypertension presented with intermittent per rectal bleeding for two weeks, which progressed to the passage of a large number of blood clots and fresh blood. He had features of class III shock on admission. An endoscopic evaluation followed initial resuscitation to locate the source of bleeding. Colonoscopy revealed a large blood clot at the opening of the appendicular orifice with no active bleeding. Oesophagoduodenoscopy, contrast-enhanced CT abdomen, and CT angiogram findings were unremarkable. Due to repeated episodes of rebleeding leading to haemodynamic instability, an exploratory laparotomy was performed. A retrocaecal appendix was noticed with a macroscopically suspicious-looking dilated tip adhered to the posterior caecal wall. Right hemicolectomy was performed as the lesion was suspicious and to stop bleeding from the site. Ileocolic side-to-side hand-sewn anastomosis was performed using 3/0 polyglactin. Postoperatively, per rectal bleeding was settled. Microscopy revealed appendiceal mucinous adenocarcinoma with AJCC staging of pT3NoMx. The patient was discharged on postoperative day seven and referred to oncological management. He was offered six cycles of chemotherapy with capecitabine and oxaliplatin. At the six-month follow-up visit, the patient had no features of recurrence clinically. Conclusion. Mucinous adenocarcinoma of the appendix can rarely present as life-threatening lower GI bleeding. Prompt resuscitation, endoscopic evaluation, and operative management with right hemicolectomy and chemotherapy provided a good outcome.